Effects of chronic exposure to head impacts on the balance function of combat sports athletes - Follmer, B.; Varga, A. A.; Herrmann, K. B.; Sun, Y.; Zehr, E. P. (Translational Sports Medicine, 2021)
We investigated static and dynamic balance in combat sport athletes chronically exposed to head impacts. MMA, boxing, kickboxing, and Muay Thai athletes exposed (AE: n = 19; 14 men, 5 women; 30.2 ± 4.5 years; 1.76 ± 0.1 m; 75 ± 9.2 kg) to head impacts were compared to athletes non-exposed (AnE: n = 25; 18 men, 7 women; 25.1 ± 3.2 years; 1.78 ± 0.1 m; 77.4 ± 10.3 kg), and control individuals (CON: n = 23, 13 men, 10 women; 25.5 ± 5.8 years; 1.75 ± 0.1m; 70.4 ± 12 kg). Static balance was assessed using the Balance Error Scoring System, and dynamic function by center of pressure shift and reactive object tracking. A low-cost balance board was used for both protocols. AE performed worse than CON (0.01 ± 0.006 vs 0.006 ± 0.003; P = .02, d = 0.75) in the ellipse area of sway for double-leg stance in firm condition (F2,62 = 3.94, P = .02, ?2 = 0.11). Static center of pressure and dynamic balance did not differ among groups. The integration of a balance board and a widely used clinical protocol unveiled differences in the ellipse area of static postural sway in the double-leg stance over a firm surface in athletes chronically exposed to head impacts. The combined use of practical, objective, and clinically relevant test protocols is encouraged to detect lasting deficits in static and dynamic balance as a result of chronic exposure to repetitive head impacts.